2021
DOI: 10.1371/journal.pone.0249633
|View full text |Cite
|
Sign up to set email alerts
|

Climatic change and extinction risk of two globally threatened Ethiopian endemic bird species

Abstract: Climate change is having profound effects on the distributions of species globally. Trait-based assessments predict that specialist and range-restricted species are among those most likely to be at risk of extinction from such changes. Understanding individual species’ responses to climate change is therefore critical for informing conservation planning. We use an established Species Distribution Modelling (SDM) protocol to describe the curious range-restriction of the globally threatened White-tailed Swallow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…Habitat suitability increased with rise in warmest quarter precipitation (above 1000 mm), coldest quarter precipitation between 50 and 100 mm, and warmest quarter temperature between 20 and 30°C. High influence of the maximum temperature of the warmest months and precipitation of the driest quarter is consistent with the other studies that have reported factors influencing habitat suitability of endemic birds, such as in Ethiopia (Bladon et al, 2021). Tropical birds are projected to be especially susceptible to rainfall‐dependent variables and extreme weather events (Şekercioğlu et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Habitat suitability increased with rise in warmest quarter precipitation (above 1000 mm), coldest quarter precipitation between 50 and 100 mm, and warmest quarter temperature between 20 and 30°C. High influence of the maximum temperature of the warmest months and precipitation of the driest quarter is consistent with the other studies that have reported factors influencing habitat suitability of endemic birds, such as in Ethiopia (Bladon et al, 2021). Tropical birds are projected to be especially susceptible to rainfall‐dependent variables and extreme weather events (Şekercioğlu et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…To present a variety of diverse climate change outcomes by the end of the century, SSPs provide a set of scenarios (SSP1, SSP2, SSP3, SSP4, and SSP5) (Hausfather & Peters, 2020). Utilizing global climate models through species distribution modeling (SDM) can predict current and future suitable habitats for species, which is useful for the formulation of conservation strategies (Baral et al, 2023; Bhandari et al, 2022; Bladon et al, 2021; Coetzee et al, 2009; Sierra‐Morales et al, 2021). SDMs are also useful tools in ecology that are frequently used for predicting species risk zones and forecasting the effects of past and future climate change on species and communities (Elith & Leathwick, 2009; Guillera‐Arroita et al, 2015; Sofaer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the endangered psittacid Amazona vinacea which presented the smallest suitable area in the baseline (10,528 km 2 ) is projected to contract its range an average of 75.7%, while widely distributed birds (>80,000 km 2 ) may expand their suitable areas up to 25% in future scenarios. Indeed, geographic range size is a trait often considered in the literature as a good predictor of birds' range shift (e.g., Avalos & Hernández, 2015; MacLean & Beissinger, 2017; Prieto‐Torres et al, 2020; Bladon et al, 2021). However, despite the possibility of those species to find areas potentially suitable in the future, the ongoing conversion of the Atlantic Forest into agricultural lands (MapBiomas, 2021; Oliveira‐Silva et al, 2022) is worrisome, mainly for frugivorous birds presenting certain ecological features such as game birds (e.g., guans) and species destined to illegal trade (e.g., parrots and toucans).…”
Section: Discussionmentioning
confidence: 99%
“…As well as the general tendency in ecology, in ornithology most studies on niche also have focused on evolutionary aspects or on invasive species. Moreover, several studies have focused on niche-tracking under climate change by a correlative modeling approach (e.g., species distribution models [33]) in order to predict future changes in species distributional range [34][35][36][37][38]. Both the niche-tracking concept and its application in predictive species distribution modeling assume niche conservatism [5], which implies that in the future a species will occupy the same environmental conditions that it occupies today.…”
Section: Introductionmentioning
confidence: 99%